Cerebral gray matter volume changes in patients with anti-N-methyl-D-aspartate receptor encephalitis: A voxel-based morphometry study - Long, Qijia; Lv, Zongxia; Zhao, Jingyuan; Shi, Ke; Li, Chunyan; Fan, Binglin; Zheng, Jinou (Frontiers in Neurology, 2022)
Background: Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is an autoimmune disease with typical clinical features. Whether and how cerebral gray matter structural damage inherent to the disorder affects cognitive function in patients is still unclear. Therefore, we aimed to explore changes in cerebral gray matter volume and whether these alterations contribute to cognitive impairment and mood disorders. Methods: Forty patients with anti-NMDAR encephalitis and forty healthy controls (HCs) matched for gender, age, and education were recruited. All participants underwent attention network tests (ANT), neuropsychological tests and an MRI scan. We performed voxel-based morphological analysis (VBM) and correlation analysis in all participants. Finally, according to the course of disease, patients were divided into two groups: NMDARE_SD (short duration; course≤2 years since diagnosis) and NMDARE_LD (long duration; course >2 years since diagnosis), to evaluate gray matter volume changes that differ as a function of disease course. Results: Compared with HCs, patients with anti-NMDAR encephalitis showed decreased executive control ability and lower MoCA score, and increased anxiety and depression as reflected by HAMA and HAMD24 scores (all p<0.05). In VBM analysis, patients showed decreased gray matter volume in bilateral thalamus, left medial prefrontal cortex (mPFC_L), left superior temporal gyrus (STG_L), and left rectus gyrus. In the analysis stratified by disease course, the NMDARE_LD group exhibited decreased gray matter volume in left precuneus, and right posterior cerebellar lobe compared to the NMDARE_SD group. Conclusions: Patients with anti-NMDAR encephalitis have cognitive, executive, and emotional dysfunction, and the sites of gray matter atrophy are concentrated in the thalamus, frontal lobe, and temporal lobe. These abnormalities may be involved in the process of cognitive and affective dysfunction. Patients with different courses of anti-NMDAR encephalitis have different brain atrophy sites. These results may help to clarify the contradiction between clinical and imaging manifestations of anti NMDAR encephalitis, which is worthy of further longitudinal observation research.